PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN BERBASIS PROYEK SOSIAL UNTUK MENUMBUHKAN EMPATI DAN KEPEDULIAN LINTAS AGAMA - Tryastuti Wuryandari (STT Bethel Indonesia Jakarta, 2025)
This study analyzes social project-based Christian Religious Education in fostering students’ empathy and interreligious care. It employed a descriptive qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, activity documentation, and students’ written reflections, then analyzed thematically through reduction, categorization, interpretation, and triangulation. The findings show that social projects shift Christian Religious Education from informative instruction toward active, collaborative, reflective, and contextual learning. Direct encounters with interreligious communities develop students’ cognitive, affective, and practical empathy. Theological reflection helps students interpret Christian love as social action that respects human dignity. This model is relevant for Christian education in plural societies because it strengthens faith identity while promoting cooperation, tolerance, and solidarity among diverse religious communities.